The Effect of Ethanol Extract of Sweet Leaves (Sauropus androgynus (L.) Merr.) to The Mortality of Anopheles aconitus L. Third Instar Larvae - Purnomo, Adi; Haryati, Sri; Sakiman, FX Bambang Sukilarso (Nexus Biomedika, 2016)
Introduction: Use of chemical insecticide to kill Anopheles aconitus L. mosquitoes can cause many side effects and resistances for the mosquitoes, thus natural larvicide is needed to kill Anopheles aconitus L. larvae. Sweet leaves contain substances that can be used as larvicide. Therefore, the aim of research is to investigate how ethanol extract of sweet leaves affects to the mortality of Anopheles aconitus L. third instar larvae. Methods: This research used laboratory experimental design with posttest only controlled group design. The subject of this research was Anopheles aconitus L. third instar larva which was divided into 7 groups. Each group contained 25 larvae and the research was repeated 4 times. The negative control group contained 100 ml of water only. The other six groups contained different number of ethanol extract of sweet leaves: 0.06%, 0.14%, 0.22%, 0.30%, 0.38%, and 0.46% (mg/100ml). Observation was done after 24 hours and the number of dead larvae was counted. Linear Regression and Probit Regression were used to analyze data. Results: Linear Regression test showed that increasing of the ethanol extract of sweet leaves affected to the increasing of Anopheles aconitus Lâ mortality based on Y = 0.02 + 2.12X formula. The R correlation score was 0.98 and R2 score was 0.96 thus it meant that percentage of ethanol extract of sweet leaves (Sauropus androgynus (L.) Merr.) to kill larvae was 96% and the rest 4% was affected by other variables. Probit Regression test showed that LC50 was at 0.19% mg and LC99 was at 0.56%. Conclusion: Ethanol extract of sweet leaves (Sauropus androgynus (L.) Merr.) has effect to the mortality of Anopheles aconitus L. third instar larvae paralleled to the increasing of ethanol extract. The LC50 is at 0.19%, the LC99 is at 0.56% Keywords: sweet leaves (Sauropus androgynus (L.) Merr.), Anopheles aconitus L. third instar larvae, mortalityÂ